Agent-Oriented Software Engineering X 10th International Workshop, AOSE 2009, Budapest, Hungary, May 11-12, 2009, Revised Selected Papers - Gleizes, Marie-Pierre.; Gomez-Sanz, Jorge J.; SpringerLink (Online service). (Berlin, Heidelberg Springer Berlin Heidelberg, 2011)
This volume constitutes the thoroughly refereed post-conference proceedings of the 10th International Workshop on Agent-Oriented Software Engineering, AOSE 2009, held in Budapest, Hungary, in May 2009 as part of AAMAS 2009, the 8th International Conference on Autonomous Agents and Multiagent Systems. The 10 revised full papers presented were carefully selected from numerous initial submissions during two rounds of reviewing and improvement. The papers have been organized into three sections on multi-agent organizations, concrete development techniques, and - one step higher - going beyond the concrete technique and proposing a development method for designing concrete types of systems. This state-of-the-art survey is rounded off by five additional lectures ressing key areas in development: agent-oriented modelling languages, implementation of MAS, testing of MAS, software processes, and formal methods for the development of MAS. They permit analysis of the current state in the generation of specifications of MAS, the way these specifications can be implemented, how they can be validated, and what steps are necessary to do so.
Electronic reproduction>
Keywords: Computer science; Computer Communication Networks; Software engineering; Logic design; Artificial intelligence; Electronic books